The analysis of corporate social responsibility of islamic banks in the Indonesia by using islamic social reporting index - Muhammad Arfan; Futri Muliyati Hisda (Proceedings of AICS - Social Sciences, 2013)
The purpose of this research is to analyze the corporate social responsibility of islamic bank by using islamic social reporting (ISR) index.The research was conducted on Islamic banks listed at Bank Indonesia in 2009, 2010, and 2011. The reaserch type used is descriptive reasearch by using content analysis method.The population of this research are islamic banks listed at Bank Indonesia in 2009-2010. After being observed, the total population are26 islamic banks for three years observation.The source of data is secondary data which is obtained from annual report for the book year ended December 31, 2009, 2010, and 2011.The results of this research showthatthe corporate social responsibility of islamic banks in Indonesia is so variative.Generally, based on themes of ISR index, the corporate social responsibility of 5 islamic banks is low in 2009. While in 2010, the corporate social responsibility of 10 islamic banks is among medium-high, and also it was happened in 2011. There are six themes in ISR index i.e. funding/investment, product/service, employee, society, environment,and good corporate governance.ISR index for product/service andgood corporategovernance are the highest theme each year. While, funding/investment and environment are stabil. Then, employee andsociety increase 10% in 2010. It means that the social activity of islamic banks is organized consistently and going sustainability.Keywords: Corporate social responsibility, islamic social reporting index, and islamic banks.